Predictive factors contributing to strain and burden among Jordanian's caregivers in chronic disease - Ahmad B Al-Rawashdeh; Rafi Alnjadat; Adam Mahmoud Khraisat (Wolters Kluwer Medknow Publications, 2023)
Background: It is well known that caregivers are at risk of suffering from diseases, including chronic ones, which might increase the burden of the healthcare worker. Materials and Methods: A cross-sectional study was conducted in Jordan on 143 caregivers who were randomly selected to participate in self-administered Quality of Life in Life-Threatening Illness-Family Carer Version (QOLLTI-F) questionnaire. The variables were tested using simple linear regression analyses in the SPSS. Results: Male Jordanian caregivers who provide unpaid care, reported lower quality of life than their female counterparts (p = 0.028), (p = 0.077), respectively. A high statistically significant result was found between unshared and shared care (p = 0.009). Statistically significant results were determined between single caregivers compared with those who were married or divorced (p = 0.894 and P = 0.041, respectively). Conclusions: This study concludes that gender, care status, type of care, and marital status are direct predictors of quality of life among Jordanian caregivers.